Detrimento patrimonial de la ciudad de Bogotá en la última década por los llamados elefantes blancos (2014)
In recent administrations Bogotá has been immersed in a number of works which begin but never end therefore has no use or benefit to the public on the contrary, has led to a capital expense of billions, combines a corruption and maladministration where citizens are forced to pay taxes, go through physical and moral needs because of the mismanagement of the rulers is also clear that the so-called white elephants abound not only in the city Bogota, but throughout the Colombian territory.